Nanometer annular manganese oxide, preparation method thereof and lithium / sodium / zinc ion secondary battery
By hydrothermal treatment in a mixed solution of manganese salt, copper salt, potassium permanganate and strong alkali, a regular morphological nanocyclic manganese oxide was prepared, which solved the problem of insufficient performance of lithium/sodium/zinc ion battery electrode materials. , achieving high capacity and good stability of battery performance.
Patent Information
- Application Number
- CN202411351425.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art lacks a method for preparing a regular morphological layered manganese oxide nanoring with low cost, simple operation and controllability, which is used for lithium/sodium/zinc ion secondary battery electrode materials, resulting in material properties and Performance is not fully utilized.
By mixing soluble manganese salts, copper salts, potassium permanganate and strong alkalis, aging and hydrothermal treatment, combined with freeze-drying and heat treatment, uniform nanocyclic manganese oxides are prepared as lithium/sodium/zinc ion batteries. the positive electrode material.
The regular morphology and high dispersion of manganese oxides are achieved, the capacity and discharge voltage platform of lithium/sodium/zinc ion batteries are improved, and the cycle stability is good, suitable for large-scale production.
Smart Images

Figure CN119191357A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials, and in particular to a nano-annular manganese oxide and a preparation method thereof, and a lithium / sodium / zinc ion secondary battery. Background Art
[0002] As an important inorganic functional material, manganese oxide has a special physical and chemical property that makes it have broad application prospects in the fields of catalysis, ion exchange, selective adsorption, biosensors, secondary batteries and supercapacitors. Birnessite-type layered manganese oxide is composed of the basic structural unit MnO6 octahedron connected by sharing edges. There are water molecules and exchangeable cations such as Na between the nanolayers. + and K + , forming a layered manganese oxide with an interlayer spacing of about 0.69-0.71nm. Since part of the manganese (III) replaces the position of the manganese (IV) atoms, or the manganese (IV) atoms migrate, the manganese oxide nanosheets are negatively charged, or there are many defects and vacancies. The generation of negative charges and atomic vacancies has a great influence on the structure and properties of the material. Compared with various tunnel-type manganese oxide materials, layered manganese oxide materials have excellent ion exchange properties and are more ideal electrode materials for secondary batteries and supercapacitors.
[0003] The results show that the structure, morphology, dimension and specific surface area of layered manganese oxide materials have a great influence on their properties. In recent years, the research work of controlling the morphology of manganese oxide to improve its properties has received great attention. The preparation methods of birnessite-type layered manganese oxide materials mainly include hydrothermal method, microwave method, redox precipitation method, high temperature solid phase method, sol-gel method and electrochemical deposition method. The reaction methods include Mn 2+ Oxidation, MnO4 - Reduction of Mn 2+ With MnO4 - Through the redox reaction between the layers, layered manganese oxide with different structures and morphologies is obtained by different preparation methods. The morphologies of layered manganese oxide include nanowires, nanobelts, nanosheets, nanowalls, nanoflower balls and hexagonal prisms, while the research and preparation of manganese oxide nanorings with regular morphology and high dispersion has not been reported yet.
[0004] In view of this, the present application aims to provide a regular morphology and highly dispersed layered manganese oxide nanoring with low cost, simple operation and strong morphology controllability, a preparation method thereof and a lithium / sodium / zinc ion secondary battery. Summary of the invention
[0005] To solve the above problems, the present invention provides a nano-ring-shaped manganese oxide and a preparation method thereof and a lithium / sodium / zinc ion secondary battery. The nano-ring-shaped manganese oxide has a uniform morphology and a size of about 2-5 μm. It is assembled into a lithium / sodium ion battery as an electrode material and has the characteristics of high capacity, high discharge voltage platform and good cycle stability, which can better meet application requirements.
[0006] The technical solution adopted by the present invention is:
[0007] A method for preparing nano-ring-shaped manganese oxide comprises the following steps:
[0008] (1) Mix soluble manganese salt, copper salt, potassium permanganate, strong alkali and deionized water;
[0009] (2) aging the mixed solution;
[0010] (3) The mixture obtained in step (2) is subjected to hydrothermal treatment, washed to neutrality, and freeze-dried to obtain manganese oxide nanorings.
[0011] Furthermore, the specific steps of mixing the soluble manganese salt, copper salt, potassium permanganate and water in step (1) are:
[0012] (a) dissolving soluble manganese salt, copper salt and potassium permanganate in deionized water respectively;
[0013] (b) rapidly adding the mixed solution and the concentrated strong alkali solution into the permanganate solution;
[0014] Furthermore, the method of rapidly mixing the manganese salt, the copper salt and the permanganate in step (1) further comprises: (c) rapidly stirring the mixed solution of the manganese salt and the copper salt and the strong alkali solution;
[0015] Preferably, the stirring conditions include: temperature of 10-90°C, time of 1-6h, speed of 1000-4000rpm;
[0016] Further preferably, the stirring conditions include: temperature of 20-30°C, time of 10-15h, and speed of 3000-4000rpm.
[0017] Furthermore, in step (3), the aged mixture is subjected to hydrothermal treatment in a stainless steel reactor lined with polytetrafluoroethylene, naturally cooled to room temperature, filtered, washed with deionized water until neutral, and vacuum dried to obtain Mn 1-x Cu x O2 nanoring;
[0018] Preferably, the hydrothermal conditions include: temperature of 150-180°C and time of 12-48h;
[0019] More preferably, the stirring conditions include: temperature of 175° C. and time of 48 h.
[0020] Furthermore, the sample obtained in step (3) is heat treated at 400-600° C. for 2-8 hours under a nitrogen or argon protective atmosphere.
[0021] Furthermore, the manganese salt is selected from at least one of manganese nitrate, manganese chloride and manganese sulfate, preferably manganese chloride; the strong base is sodium hydroxide or potassium hydroxide; the copper salt is selected from at least one of copper nitrate, copper chloride and copper sulfate;
[0022] Specifically, in step (1), the molar ratio of divalent manganese to divalent copper is 8 to 10;
[0023] The molar ratio of the divalent manganese salt to the high-valent manganese salt is 1.5-2.4:1, preferably 1.8-2.2:1, and more preferably 1.9:1.
[0024] Further, among them,
[0025] The molar ratio of the sum of the moles of the divalent manganese salt and the copper salt to the permanganate is 1.5-2.5, preferably 2.0-2.2;
[0026] The concentration of the strong base is 10-20 mol / L, preferably 15-20 mol / L;
[0027] Concentration of potassium permanganate: 0.1-0.5mol / L.
[0028] Based on the same inventive concept, the present application also provides a nano-annular manganese oxide prepared according to the above preparation method.
[0029] Furthermore, the manganese oxide exists in the form of nano rings, and the diameter of the nano rings is 2 to 5 μm.
[0030] Based on the same inventive concept, the present application also provides a lithium / sodium / zinc ion battery, which includes a positive electrode, a negative electrode and an electrolyte, and is characterized in that the material of the positive electrode includes the above-mentioned manganese oxide.
[0031] The beneficial effects of the present invention are as follows:
[0032] 1. The preparation method provided by the present application comprises the following steps: (1) mixing a soluble manganese salt, a copper salt, potassium permanganate, a strong base and deionized water; (2) aging the mixed solution; (3) charging the solution of step (2) into a reactor, performing hydrothermal treatment and washing until neutral; (4) performing heat treatment on the sample obtained in step (3). The preparation method is simple in steps, easy to prepare and easy to mass produce, and the prepared nano-ring-shaped manganese oxide has a regular morphology and a uniform particle size distribution.
[0033] 2. The manganese oxide provided in this application has a uniform nano-ring morphology with a size of about 2-5 μm and high dispersibility. It can be used as an electrode material to assemble lithium / sodium / zinc ion batteries with high capacity, high discharge voltage platform, good cycle stability and good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The Mn prepared in Example 1-3 1-x Cu x X-ray diffraction pattern of O2 nanorings;
[0035] Figure 2 The Mn prepared in Example 1 1-x Cu x Field emission scanning electron microscopy image of O2 nanorings;
[0036] Figure 3 The Mn prepared in Example 1 1-x Cu x EDS spectrum analysis of O2 nanoring;
[0037] Figure 4 The Mn prepared in Example 2 1-x Cu x SEM images of O2 nanorings;
[0038] Figure 5 The Mn prepared in Example 3 1-x Cu x SEM images of O2 nanorings;
[0039] Figure 6 The Mn prepared in Example 4 1-x Cu x SEM images of O2 nanorings;
[0040] Figure 7 This is a scanning electron microscope photograph of the MnO2 nanobelt prepared in Comparative Example 1;
[0041] Figure 8 The Mn prepared in Example 1 1-x Cu x Lithium-ion battery charge and discharge curves of O2 nanorings;
[0042] Fig. 9 The Mn prepared in Example 1 1-x Cu x Charge and discharge curves of zinc-ion battery with O2 nanorings. DETAILED DESCRIPTION
[0043] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively by way of examples, and preferred embodiments of the present invention are given below. However, the present invention can be implemented in a variety of different forms and is not limited to the embodiments described herein. Any other implementation schemes obtained by modifying or equivalently replacing the technical scheme of the present invention without creative results are within the protection scope of the present invention.
[0044] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for describing specific embodiments and are not intended to limit the present invention.
[0045] The numerical values disclosed in the embodiments of the present invention are approximate values, not definite values. When the error or experimental conditions permit, all values within the error range may be included without being limited to the specific numerical values disclosed in the embodiments of the present invention.
[0046] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0047] Example 1
[0048] This embodiment provides a method for preparing manganese oxide, comprising the following steps:
[0049] (1) Dissolve 1.9791 g (9 mmol) of MnCl2·4H2O and 0.1345 g (1 mmol) of CuCl2 in 10 mL of water and let stand for use;
[0050] (2) Dissolve 0.7902 g (5 mmol) of KMnO4 in 140 mL of deionized water. After stirring to completely dissolve, quickly add 168.3169 g of potassium hydroxide solid and stir rapidly until it is completely dissolved. Quickly add manganese chloride solution to the above solution and stir at room temperature for 2 hours. Wait until the solution temperature drops to room temperature.
[0051] (3) The obtained mixture was placed in a stainless steel reactor lined with polytetrafluoroethylene and subjected to hydrothermal treatment at 175° C. for 36 hours, naturally cooled to room temperature, filtered, washed with deionized water until neutral, and freeze-dried to obtain manganese oxide nanorings.
[0052] Method for preparing lithium ion secondary battery
[0053] The prepared material was mixed with a conductive agent Super-p, a binder polyacrylic acid (PAALi) and deionized water in a mass ratio of 70:20:10:100, stirred evenly to obtain a stable and uniform slurry, coated on the surface of a copper foil, and dried at 85°C to obtain a pole piece, combined with a metal lithium sheet, an electrolyte of 1 mol / L LiPF6, a solvent of EC:PC:DEC.EMC, a volume ratio of 1:0.3:1:1, and a diaphragm of a three-layer diaphragm of PP / PE / PP with a thickness of 12 um to make a button battery for testing the specific capacity of the material.
[0054] Zinc-ion battery assembly:
[0055] The above materials, conductive agent and binder are dispersed in a solvent with a mass percentage of 80%, 10% and 10% respectively to obtain a positive electrode active slurry; the positive electrode active slurry is coated on a titanium foil and vacuum dried to obtain a positive electrode plate; wherein the conductive agent is acetylene black, the binder is polyvinyl fluoride, and the solvent is N-methylpyrrolidone. The positive electrode plate, the diaphragm and the negative zinc plate are sequentially loaded into the shell and injected with a 2mol / L zinc sulfate electrolyte to obtain a button-type zinc ion secondary battery; wherein the negative electrode plate is polished metal zinc, the diaphragm is Celgard 3000, and the electrolyte is a 2mol / L ZnSO4 aqueous solution.
[0056] Example 2
[0057] This embodiment provides a method for preparing manganese oxide, comprising the following steps:
[0058] (1) Dissolve 1.9791 g (10 mmol) of Mn(NO3)2·4H2O and 0.375 g (2 mmol) of Cu(NO3)2 in 10 mL of water and let stand for use;
[0059] (2) Dissolve 0.7902 g of KMnO4 in 140 mL of deionized water, stir until completely dissolved, quickly add 90.00 g of sodium hydroxide solid, stir quickly until completely dissolved, quickly add manganese chloride solution to the above solution, stir at room temperature for 2 hours, and wait until the solution temperature drops to room temperature;
[0060] (3) The obtained mixture was placed in a stainless steel reactor lined with polytetrafluoroethylene and subjected to hydrothermal treatment at 180° C. for 24 hours, naturally cooled to room temperature, filtered, washed with deionized water until neutral, and freeze-dried to obtain manganese oxide nanorings.
[0061] Method for preparing secondary battery
[0062] The prepared material was mixed with a conductive agent Super-p, a binder polyacrylic acid PAALi and deionized water in a mass ratio of 70:20:10:100, stirred evenly to obtain a stable and uniform slurry, coated on the surface of copper foil, and dried at 85°C to obtain a negative electrode plate. The metal lithium plate was matched, the electrolyte was 1 mol / L LiPF6, the solvent was: EC:PC:DEC.EMC, the volume ratio was 1:0.3:1:1, and the diaphragm was a three-layer diaphragm of PP / PE / PP with a thickness of 12um. Button batteries were made to test the capacity and initial efficiency of the material.
[0063] Example 3
[0064] This embodiment provides a method for preparing manganese oxide, comprising the following steps:
[0065] (1) Dissolve 1.9791 g (9 mmol) of MnCl2·4H2O and 0.1248 g (0.5 mmol) of Cu(SO4)2·5H2O in 10 mL of water and let stand for use.
[0066] (2) Dissolve 0.7902 g (5 mmol) of KMnO4 in 140 mL of deionized water. After stirring until completely dissolved, quickly add 151.4852 g of potassium hydroxide solid and stir rapidly until completely dissolved. Quickly add manganese chloride solution to the above solution and stir at room temperature for 2 hours until the solution temperature drops to room temperature.
[0067] (3) The obtained mixture was placed in a stainless steel reactor lined with polytetrafluoroethylene and subjected to hydrothermal treatment at 150° C. for 48 hours, naturally cooled to room temperature, filtered, washed with deionized water until neutral, and freeze-dried to obtain manganese oxide nanorings.
[0068] Method for preparing secondary battery
[0069] The prepared material was mixed with a conductive agent Super-p, a binder polyacrylic acid (PAALi) and deionized water in a mass ratio of 70:20:10:100, stirred evenly to obtain a stable and uniform slurry, coated on the surface of a copper foil, and dried at 85°C to obtain a negative electrode sheet. A metal lithium sheet was used, the electrolyte was 1 mol / L LiPF6, the solvent was EC:PC:DEC.EMC, the volume ratio was 1:0.3:1:1, and the diaphragm was a three-layer diaphragm of PP / PE / PP with a thickness of 12 um. A button battery was made to test the electrical properties of the material.
[0070] Example 4
[0071] This embodiment provides a method for preparing manganese oxide, comprising the following steps:
[0072] (1) Dissolve 1.9791 g (9 mmol) of MnCl2·4H2O and 0.2018 g (1.5 mmol) of CuCl2 in 10 mL of water and let stand for use.
[0073] (2) Dissolve 0.6479 g (4.1 mmol) of KMnO4 in 140 mL of deionized water. After stirring until completely dissolved, quickly add 168.3169 g of potassium hydroxide solid and stir rapidly until completely dissolved. Quickly add manganese chloride solution to the above solution. Stir at room temperature for 2 hours until the solution temperature drops to room temperature.
[0074] (3) The obtained mixture was placed in a stainless steel reactor lined with polytetrafluoroethylene and subjected to hydrothermal treatment at 175° C. for 48 hours, naturally cooled to room temperature, filtered, washed with deionized water until neutral, and freeze-dried to obtain manganese oxide nanorings.
[0075] Method for preparing secondary battery
[0076] The prepared material was mixed with a conductive agent Super-p, a binder polyacrylic acid PAALi and deionized water in a mass ratio of 70:20:10:100, stirred evenly to obtain a stable and uniform slurry, coated on the surface of a copper foil, and dried at 85°C to obtain a negative electrode sheet. The electrolyte was 1 mol / L LiPF6, the solvent was EC:PC:DEC.EMC, the volume ratio was 1:0.3:1:1, and the diaphragm was a three-layer diaphragm of PP / PE / PP with a thickness of 12 um. A button battery was made to test the electrical properties of the material.
[0077] Comparative Example 1
[0078] This comparative example provides a method for preparing manganese oxide, comprising the following steps:
[0079] (1) Dissolve 1.9791 g (10 mmol) of MnCl2·4H2O in 10 mL of water and let stand for use;
[0080] (2) Dissolve 0.8318 g (9 mmol) of KMnO4 in 140 mL of deionized water, stir until completely dissolved, quickly add 168.3169 g of potassium hydroxide solid, stir quickly until completely dissolved, quickly add manganese chloride solution to the above solution, stir at room temperature for 2 hours, and wait until the solution temperature drops to room temperature;
[0081] (3) The obtained mixture was placed in a stainless steel reactor lined with polytetrafluoroethylene and subjected to hydrothermal treatment at 175° C. for 48 hours, naturally cooled to room temperature, filtered, washed with deionized water until neutral, and freeze-dried to obtain manganese oxide nanorings.
[0082] Method for preparing secondary battery
[0083] The prepared material was mixed with a conductive agent Super-P, a binder polyacrylic acid PAALi and deionized water in a mass ratio of 70:20:10:100, stirred evenly to obtain a stable and uniform slurry, coated on the surface of a copper foil, and dried at 85°C to obtain a negative electrode sheet. The electrolyte was 1 mol / L LiPF6, the solvent was EC:PC:DEC.EMC, the volume ratio was 1:0.3:1:1, and the diaphragm was a three-layer diaphragm of PP / PE / PP with a thickness of 12 um. A button battery was made to test the full battery performance of the material.
[0084] The inventors characterized the products obtained in Examples 1-4 and Comparative Example 1, and performed XRD phase analysis using a RigakuminiFlex600 powder diffractometer. The test conditions were: Cu target Ka line, Ni filter, voltage 40KV, current 15mA, scanning range 5°~80°(2θ), and scanning speed 10° / min. The morphology was observed using a Quanta600F field emission scanning electron microscope with an acceleration voltage of 200kV.
[0085] As can be seen from the figure, the products obtained in Examples 1-4 of the present invention are all highly crystalline Birnessite-type layered Mn 1- x Cu x O2 (0≤x≤0.2), the obtained layered manganese oxide has a nano-ring morphology. The obtained hexagonal layered manganese oxide has single crystal characteristics, and the interlayer spacing is 0.71nm. The average valence of the manganese element in the layered manganese oxide is 3.8, the particles are evenly distributed and have good dispersibility; the particle size is about 2-5um, and the ring diameter is about 150-200nm. In contrast, in Example 1, the nano-belt products were respectively used, and the morphology of the obtained products did not show nano-rings, and the rigidity was strong, and fragments were clearly visible.
[0086] In addition, see Table 1 below, which shows the performance test results of the lithium ion batteries in Examples 1-4 and Comparative Example 1.
[0087] Table 1 Performance test table of lithium ion batteries made by embodiments and comparative examples
[0088]
[0089] As can be seen from the above table, the nano-annular manganese oxide provided in the present application is used as an electrode material and assembled into a lithium-ion battery, which has high capacity, a high discharge voltage platform, and good cycle stability, and can better meet application requirements.
[0090] In summary, the nano-ring manganese oxide provided by the present application has a simple preparation step, is easy to prepare, and is easy to mass produce. The prepared nano-ring manganese oxide has a regular morphology and a uniform particle size distribution. 1-x Cu x O2 (0≤x≤0.2) has a uniform nanoring morphology and a size of about 2-5um. It has high dispersibility and can be used as an electrode material to assemble lithium / sodium / zinc ion batteries with high capacity, high discharge voltage platform, good cycle stability and good application prospects.
[0091] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing nano-ring-shaped manganese oxide, characterized in that: The following steps are involved: (1) Mix soluble manganese salt, copper salt, potassium permanganate, strong alkali and deionized water; (2) aging the mixed solution; (3) The mixture obtained in step (2) is subjected to hydrothermal treatment, washed to neutrality, and freeze-dried to obtain manganese oxide nanorings.
2. The method for preparing nano-annular manganese oxide according to claim 1, characterized in that: The specific steps of mixing the soluble manganese salt, copper salt, potassium permanganate and water in step (1) are as follows: (a) dissolving soluble manganese salt, copper salt and potassium permanganate in deionized water respectively; (b) adding the mixed solution of the manganese salt and the copper salt and the concentrated strong alkali solution to the permanganate solution.
3. The method for preparing nano-annular manganese oxide according to claim 2, characterized in that: The specific step of quickly mixing the manganese salt, the copper salt and the permanganate in step (1) also includes: (c) rapidly stirring the manganese and copper salt solutions and the strong base solution; Preferably, the stirring conditions include: temperature of 10-90°C, time of 1-6h, speed of 1000-4000rpm; Further preferably, the stirring conditions include: temperature of 20-30°C, time of 10-15h, and speed of 3000-4000rpm.
4. The method for preparing nano-annular manganese oxide according to claim 1, characterized in that: In step (3), the aged mixture is subjected to hydrothermal treatment in a stainless steel reactor lined with polytetrafluoroethylene, cooled naturally to room temperature, filtered, washed with deionized water until neutral, and vacuum dried to obtain Mn 1-x Cu x O2(0≤x≤0.2) nanoring; Preferably, the hydrothermal conditions include: temperature of 150-180°C and time of 12-48h; More preferably, the stirring conditions include: temperature of 175° C. and time of 48 h.
5. The method for preparing nano-annular manganese oxide according to claim 1, characterized in that: The sample obtained in step (3) is heat treated at 400-600° C. for 2-8 hours under a nitrogen or argon protective atmosphere.
6. The method for preparing nano-annular manganese oxide according to claim 2, characterized in that: The manganese salt is selected from at least one of manganese nitrate, manganese chloride and manganese sulfate, preferably manganese chloride; the strong base is sodium hydroxide or potassium hydroxide; the copper salt is selected from at least one of copper nitrate, copper chloride and copper sulfate; Specifically, in step (1), the molar ratio of divalent manganese to divalent copper is 8 to 10; The molar ratio of the divalent manganese salt to the high-valent manganese salt is 1.5-2.4:1, preferably 1.8-2.2:1, and more preferably 1.9:
1.
7. The method for preparing nano-annular manganese oxide according to claim 6, characterized in that: in, The molar ratio of the sum of the moles of the divalent manganese salt and the copper salt to the permanganate is 1.5-2.5, preferably 2.0-2.2; The concentration of the strong base is 10-20 mol / L, preferably 15-20 mol / L; Concentration of potassium permanganate: 0.1-0.5mol / L.
8. A nano-annular manganese oxide prepared according to the preparation method according to any one of claims 1 to 7.
9. The nano-annular manganese oxide according to claim 8, characterized in that: The manganese oxide exists in the form of nano rings, and the diameter of the nano rings is 2 to 5 μm.
10. A lithium / sodium / zinc ion battery, comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The material of the positive electrode comprises the manganese oxide according to any one of claims 8 to 9.
